Fiber Optics Physics and Technology - Mitschke, Fedor. (Springer Berlin Heidelberg, 2010)
Telephone, telefax, email and internet -- the key ingredient of the inner workings is the conduit: the line which is designed to carry massive amounts of data at breakneck speed. In their data-carrying capacity optical fiber lines beat other technologies (copper cable, microwave beacons, satellite links) hands down, at least in the long haul. This book tells you all you want to know about optical fibers: Their structure, their light-guiding mechanism, their material and manufacture, their use. Several effects tend to degrade the signal as it travels down the fiber: they are spelled out in detail. Nonlinear processes are given due consideration for a twofold reason: On the one hand they are fundamentally different from the more familiar processes in electrical cable. On the other hand, they form the basis of particularly interesting and innovative applications, provided they are understood well enough. A case in point is the use of so-called solitons, i.e. special pulses of light which have the wonderful property of being able to heal after perturbation. The book will take you from the physical basics of ray and beam optics, explain fiber structure and the functions of optical elements, and bring you to the forefront of applications. The state of the art of high speed data transmission will be described, and the use of fiber optic sensors in metrology is treated. The book is written in a pedagogical style so that students of both physics and electrical engineering, as well as technicians and engineers involved in optical technologies, will benefit. Prof. Fedor Mitschke, a German physicist, was involved in pioneering work on fiber-optic solitons at Bell Laboratories in 1985-86. He has held teaching positions at universities in Hannover, Munich, Munster, and Rostock (all in Germany). Since 1997 he holds the chair for optics at the Institute of Physics at Rostock University. This book grew out of lectures he gave at Hannover, Munster, Rostock, and as visiting professor in Lule, Sweden.